In the land of buried tongues testimonies and literary narratives of the war of liberation of Bangladesh - Das, Chaity ca. 20./21. Jh (Oxford University Press, 2017)
This book is about testimonial and fictional narratives emerging from the War of Liberation of Bangladesh in 1971. It ended when winter came but the chill persisted for long. The spectres of war were resurrected with accounts of vigilante violence against those who opposed the liberation, predominantly Urdu speakers. The assassination of top leaders of the freedom struggle and the war, the rise of military dictatorship, the execution of Mujib's killers in 2010, and the trial and execution of Razakars recently, remind one of the deep wounds of war. War literature from Bangladesh and Pakistan continues to appear in spite of officially authorized remembrance and forgetting. In placing testimonial accounts beside fiction, a complex picture of the legacy of a violent time becomes visible. Recent studies into the war have not dealt with the fund of insights provided by the fiction that commemorates the second partition of the subcontinent. In dealing with memories and spectres of suffering, fiction helps to negotiate the "archives of silence" (Yasmin Saikia's phrase) and allows us to analyse narratives of victory and loss. In articulating the deeply gendered universe of War, the fuzzy borders between perpetrators and victims are made visible